Acute Hepatocellular Jaundice After Dofetilide Initiation: A Case Report. (February 2018) - Rose, Patrick Gary; Seabury, Robert; Cwikla, Gregory
Dofetilide's hepatotoxicity is not well described. In this case report, we describe acute hepatocellular jaundice related to dofetilide use in a 33-year-old male being treated for atrial fibrillation. Both viral and ischemic causes of hepatocellular damage were ruled out as unlikely in this case. This case report outlines a rare yet probable report of idiosyncratic dofetilide-induced liver injury.